An introduction to the ecology of early historic communal bison hunting among the Northern Plains Indians - Arthur, George W. (George William), 1926- (Mercury series., 1975)
Doctoral thesis in examining the ethno-historical reconstruction of the hunting activities of the northern Plains tribes (Blackfoot, Plains Cree, Gros Ventre, and Assiniboine) in relationship to the annual cycle of the bison in the plains prairie grassland.